Effects of age and playing position on field-based physical fitness measures in adolescent female soccer players - Hackett, D. A.; He, W.; Tran, D. L.; Sanders, R. H. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: While numerous studies have explored age and playing position effects on fitness levels in male adolescent soccer players, research on female players in this context is lacking. The purpose of this study was to examine the effects of age and playing position on field-based physical fitness measures in adolescent female soccer players, with consideration for maturity. METHODS: This cross-sectional study involved 284 females aged 12.0-15.9 years. Participants performed the 20-m multi-stage fitness test (20MSFT) to assess estimated maximum oxygen uptake (VO2max), 10-m and 20-m sprints, 505 Test to evaluate change of direction speed (CODS), the medicine ball chest throw (MBCT) and countermovement vertical jump (CMVJ) to assess muscle power. For data analysis, participants were separated into age groups (12, 13, 14, and 15 years), and playing position (forward, midfielder, defender, and goalkeeper). Age at peak height velocity was considered a covariate to account for maturity status. RESULTS: Players aged 14 years demonstrated faster CODS compared to 15 years old (P=0.014), while superior MBCT performance was noted at both ages compared to younger ages (P<0.001). Goalkeepers exhibited lower VO2max than midfielders and defenders (P<0.05). Defenders and goalkeepers exhibited greater hip circumference and body mass compared to midfielders (P=0.01), along with a larger waist circumference for defenders compared to midfielders (P=0.003). Age and position interactions were absent. When analyses were run without controlling for maturity, all results were the same except for CODS where no age effect was found. CONCLUSIONS: This study suggests that upper body power, and flexibility may be impacted by age and playing position in adolescent female soccer players, regardless of maturity status. The CODS appears to be influenced by age only when controlling for maturity.